Functional magnetic hybrid nanomaterials for biomedical diagnosis and treatment. (4th May 2017) - Tian, Xin; Zhang, Lechuan; Yang, Mo; Bai, Lei; Dai, Yiheng; Yu, Zhiqiang; Pan, Yue
Abstract : Magnetic nanomaterials integrating supplemental functional materials are called magnetic hybrid nanomaterials (MHNs). Such MHNs have drawn increasing attention due to their biocompatibility and the potential applications either as alternative contrast enhancing agents or effective heat nanomediators in hyperthermia therapy. The joint function comes from the hybrid nanostructures. Hybrid nanostructures of different modification can be easily achieved owing to the large surface‐area‐to‐volume ratio and sophisticated surface characteristic. In this focus article, we mainly discussed the design and synthesis of MHNs and their applications as multimodal imaging probes and therapy agents in biomedicine. These MHNs consisting magnetic nanomaterials with functional nanocomponents such as noble metal or isotopes could perform not only superparamagnetism but also features that can be adapted in, for example, enhancing computed tomography contrast modalities, positron emission tomography, and single‐photon emission computed tomography. The combination of several techniques provides more comprehensive information by both synergizing the advantages, such as quantitative evaluation, higher sensitivity and spatial resolution, and mitigating the disadvantages. Such hybrid nanostructures could also provide a unique nanoplatform for enhanced medical tracing, magnetic field, and light‐triggered hyperthermia. Moreover, potential advantages and opportunities will be achieved via a combination of diagnostic and therapeutic agents within a single platform, which is so‐called 'theranostics.' We expect the combination of unique structural characteristics and integrated functions of multicomponent magnetic hybrid nanomaterials will attract increasing research interest and could lead to new opportunities in nanomedicine and nanobiotechnology. WIREs Nanomed Nanobiotechnol 2018, 10:e1476. doi: 10.1002/wnan.1476 This article is categorized under: Diagnostic Tools > Diagnostic Nanodevices Abstract : Different functions of Magnetic hybrid nanomaterials with different morphologies in biomedical diagnosis and treatment.